IMPLEMENTATION OF DMAIC APPROACH TO IMPROVEMENT OF BLOCK PRESS PRODUCTION PROCESS (CASE STUDY PT. XYZ) - Wahyu Wiguna (SEAN Institute, 2022)
The limit increase in the number of product defects p there is a block press production process line in January-July 2022 by 6.5%, namely Block Press too light, Block Press sample, Block Press scratch, Block Press cracked, Block Press broke, Block Press too heavy, Block Press top uneven, Oblique Block Press, Block Press bottom uneven. The purpose of this study is to control the process so that the company's target can control the number of product defects. The DMAIC approach is used to conduct quality control analysis using production data and production errors for January- June 2022. The result of the DPMO calculation is 7222 Pc which means that there will be a chance of product defects of 7222 Pc from process failures per one million opportunities, with a block press production process sigma rate of 3.9 Sigma. The result of the DPMO calculation is 7222 Pc which means that there will be a chance of product defects of 7222 Pc from process failure per one million opportunities, with a block press production process sigma rate of 3.9. Some types of defects that are dominant in BLOCK PRESS products are: too light (38%), compel (16%), and scratch (9%). Some proposals aimed at reducing the number of product defects on the block press are: Making work standards for checking powder moisture, Supervision and control by production supervisors, Making work standards for molding filling and operator training.